Theoretical and practical engineering significance of British pendulum test. Issue 1 (2nd January 2022) - Chu, L.; Guo, Weiwei; Fwa, T. F.
ABSTRACT: The British pendulum test is commonly used to measure low-speed pavement friction and provide a measure of the quality of pavement surface micro-texture in terms of skid resistance contribution. Generally, it is considered an empirical test, and the measured British Pendulum Number (BPN) taken as an index value. The present study shows that this interpretation is a misrepresentation of the test, and that the British pendulum test is a theoretically sound test, and there exists a unique one-to-one mechanistic relationship between the measured BPN and friction coefficient. By means of a three-dimensional finite-element simulation model developed using theories of physics, it is demonstrated mechanistically that for each test surface with a known coefficient of friction, there is a unique corresponding BPN value. That is, BPN is not an empirical index, but an engineering quantity that has a mechanistic relationship with the friction coefficient of the test surface. The theoretical model makes it possible to interpret mechanistically the results of tests conducted in the field and laboratory. The theoretical soundness of the test has high practical significance in evaluating the low-speed friction coefficients of pavement materials during mix design in the laboratory, and friction management of in-service pavements.